A two-year review of necrotising enterocolitis in very low birth weight infants (<1500g) in a South African tertiary hospital - Gumede, Mbalenhle Purity (Department of Paediatrics and Child Health, 2020)
Background: There is paucity of local data on the profile of preterm very low birth weight (VLBW) infants who develop moderate to severe necrotising enterocolitis (NEC) and their outcomes. Methods: A retrospective folder review of VLBWs who developed Modified Bell’s stage II NEC or higher at Groote Schuur Hospital (GSH) nursery between January 2012 and December 2013 was performed. Outcomes were defined as requirement for surgery and mortality. Results: Forty seven infants were included (5% incidence). Gestational ages ranged from 25 to 36 weeks, 53% were 10 mg/L (60%) and subserosal gas radiologically (84%). Half the patients received mechanical ventilation, 38% required inotropes. The mortality rate was 64%. Three of the five infants that received surgery survived. Conclusion: Despite a similar incidence to global counterparts, our VLBW infants have severe NEC disease often requiring advanced life support, with a high mortality rate. HIV exposure may increase the risk of NEC development.